Pengaruh digitalisasi, literasi keuangan, dan dukungan teknologi terhadap kinerja keuangan UKM di Kota Pontianak - Yenni Emilia; Reni Dwi Widyastuti; Aris Setiawan (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2025)
Small and Medium Enterprises (SMEs) play an essential role in supporting the economy, including in the city of Pontianak. However, they still face several challenges, including low financial literacy, limited digitalization, and a lack of technological support, which continue to hinder the development of SMEs. This study aims to analyze the influence of digitalization, financial literacy, and technological support on the financial performance of SMEs in Pontianak City. The research methodology is multiple regression analysis using SPSS 26. The research sample consisted of 100 SMEs in Pontianak City. The study finds that digitalization, financial literacy, and technological support have a positive and significant effect on SME financial performance. Financial literacy is the most critical factor in improving entrepreneurs' ability to manage finances and make sound business decisions. The conclusion of this study states that digitalization, financial literacy, and technological support are essential to improving the financial performance of SMEs. The higher a business owner's financial literacy, the better their financial performance will be. Public interest statements This study provides SME entrepreneurs with an understanding of the importance of financial literacy and the use of technology to improve business performance. This research supports SMEs in increasing their competitiveness and business sustainability.